The Determinant Factors of Behavior in M-Commerce Application Usage for Online Purchasing - Wisnu Putra Prihantoro; Arif Satria; Hartoyo Hartoyo (Indonesian Journal of Business and Entrepreneurship (IJBE), 2018)
The development of technology in human life makes the process of buying and selling currently using the online system. The high electronic transactions that occur in Indonesia are driven by the number of e-commerce or companies that make m-commerce applications on smartphones. This research has several objectives, and the first goal is to know the effect of perceived usefulness, behavior of the use of m-commerce applications, subjective norms, and behavioral control of interest in m-commerce applications on smartphones on online purchases. The second goal is to analyze the ease of use of perceived usefulness, and the third objective is to analyze the effect of ease of use and perceived usefulness on the behavior of using m-commerce applications for online purchases. The fourth objective is to analyze the effect of security perception on the interest of using m-commerce application on online purchase. This research was conducted by survey method and using SEM for data analysis. The results of this research indicate that there are significant influences among the behavior of the use of m-commerce applications, perceived usefulness, and behavioral control over interest in using m-commerce applications for online purchases. Ease of use and usability positively affect the behavior of using m-commerce applications. Ease of use positively affects the perceived usefulness. The security factor has a positive effect on the interest of using m-commerce application.Keywords: e-commerce, m-commerce adoption, SEM, Technology Acceptance Model, Theory of Planned Behavior